2017
DOI: 10.1016/j.stem.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex CRISPR/Cas9-Based Genome Editing in Human Hematopoietic Stem Cells Models Clonal Hematopoiesis and Myeloid Neoplasia

Abstract: SUMMARY Hematologic malignancies are driven by combinations of genetic lesions that have been difficult to model in human cells. We used CRISPR/Cas9 genome engineering of primary adult and umbilical cord blood CD34+ human hematopoietic stem and progenitor cells (HSPCs), the cells of origin for myeloid pre-malignant and malignant diseases, followed by transplantation into immunodeficient mice, to generate genetic models of clonal hematopoiesis and neoplasia. Human hematopoietic cells bearing mutations in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 31 publications
3
63
0
1
Order By: Relevance
“…The observation that multiplex genome editing that does not rely on HDR integration of donor DNA causes chromosomal rearrangements at relatively high frequency is worrisome because many recent multiplex mutagenesis workflow rely on PCR based deep sequencing of the target allele to measure success rates ( i.e. , CRISPR-Seq ( Tothova et al 2017 )) of genome editing at multiple loci. This method cannot detect chromosomal rearrangements, and as such the events may have gone unnoticed in many experiments so far.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that multiplex genome editing that does not rely on HDR integration of donor DNA causes chromosomal rearrangements at relatively high frequency is worrisome because many recent multiplex mutagenesis workflow rely on PCR based deep sequencing of the target allele to measure success rates ( i.e. , CRISPR-Seq ( Tothova et al 2017 )) of genome editing at multiple loci. This method cannot detect chromosomal rearrangements, and as such the events may have gone unnoticed in many experiments so far.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-leukemic LT-HSCs are a source of clonal evolution within blood malignancies and can act as a reservoir of relapse after chemotherapy treatment 7 . Thus, modeling and understanding the genetic complexity and cellular heterogeneity seen in human hematological malignancies requires novel methodologies that allow genome editing in LT-HSCs and their functional read-out 3,4 .Recently several studies have demonstrated efficient gene editing of bulk CD34 + populations that are enriched for human HSPCs [8][9][10][11][12][13][14][15][16] . Highly efficient non-homologous end joining (NHEJ) mediated gene disruption of up to 80-90% efficiency has been reported in CD34 + HSPCs 10,11,14,16 .…”
mentioning
confidence: 99%
“…Additionally, a recent study described the generation of CHIP and myeloid disease models by multiplex gene editing of human CD34 + HSPCs using transient plasmid transfection (Tothova et al, 2017). In this model, myeloid malignancies showing expansion of immature myeloid cells or histiocytes emerged when multiplex gene editing was combined with the introduction of oncogenic FLT3-ITD or NPM1 mutants.…”
Section: Discussionmentioning
confidence: 99%